ANALISIS PENGEMBANGAN STRATEGI KEPUASAN NASABAH DI BANK RIAU KEPRI CABANG SYARIAH PEKANBARU - Akhyar Hasanal Arva; Wasnury Rendra; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the consumer satisfaction index and strategies to improvethe service quality of Bank Riau Kepri Pekanbaru Syariah Branch. The population in thisstudy includes all customers of Bank Riau Kepri Syariah Branch Pekanbaru with asample of 110 people with purposive sampling method. The analysis tool in this studyuses CSI (Customers Satisfaction Index) analysis and IPA (Importance PerformanceAnalysis) analysis with the help of the SPSS program. The results showed that theconsumer satisfaction index at Bank Riau Kepri Syariah Pekanbaru Branch was 82.84 orwas in the "very satisfied" degradation. The IPA analysis pays attention to the strategyfor improving the service quality of Bank Riau Kepri Syariah Pekanbaru Branch,prioritizing the following 3 indicators: Strategic location (IPA-Indicator 3); guarantee oferror-free transactions (IPA-Indicator 11); Companies can store data accurately (IPAIndicator 12). Keywords: Customer Satisfaction, Service Quality, Bank Riau Kepri Syariah PekanbaruCustomer Satisfaction Index (CSI), Importance Performance Index (IPA)